PENGARUH PROMOSI JABATAN, TUNJANGAN KINERJA DAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA KANTOR BAPPEDA LITBANG KABUPATEN PONOROGO - Yuana, Muhammad Ardino (Universitas Slamet Riyadi, 2021)
BAPEDA Litbang Ponorogo Regency in managing employees puts forward the vision and mission of innovation and the ability of employees to improve their ability to carry out their duties. The success of an organization in achieving goals cannot be separated from the role of employees. The most important resources in an organization are human resources, the people who give their energy, talents, creativity and efforts to the organization. One of the main problems in human resource management is how to find the best way to improve employee performance. Things that can affect employee performance are promotion, performance benefits, and leadership. The problem is: do promotion, performance allowances, and leadership have a significant effect on employee performance at the Ponorogo District Research and Development Agency Office? This study aims to analyze the significance of the effect of promotion, performance allowances, and leadership on employee performance at the Bappeda Research and Development Office of Ponorogo Regency. The population of this study were 60 employees at the Bappeda Research and Development Office of Ponorogo Regency. Data collection techniques using questionnaires, interviews and literature studies that have passed the validity and reliability tests. The regression requirements test uses the classical assumption test. The data analysis technique used multiple linear regression analysis and hypothesis testing was carried out by means of the t test. The results of this study indicate that promotion, performance allowances, and leadership have a positive and significant effect on employee performance at the Office of the Research and Development Planning Agency of Ponorogo Regency. The variable that has the dominant influence on the performance of employees at the Ponorogo District Research and Development Agency Office is the variable of promotion because the value of the highest coefficient.